Ethylene Gas Decomposition Using ZSM-5/WO3-Pt-Nanorod Composites for Fruit Freshness - Kim, Sunghoon; Jeong, Gyoung Hwa; Kim, Sang Wook (ACS Sustainable Chemistry and Engineering, 2019)
The harmful effect of ethylene arising from fruits and vegetables renders heavy losses of fresh-cut products resulting in environmental waste. Various strategies such as controlled atmosphere devices and ethylene scavenger packaging have been developed for extension of shelf life in postharvest commodities. The photocatalytic oxidation process for ethylene removal can be considered as a promising alternative to use of coupling with zeolite absorbents maintaining high surface area though morphological characteristics of photocatalyst nanocrystals. Herein, we developed nanocomposites composed of visible-light active Pt-loaded monoclinic WO3 nanorods on ZSM-5 (ZSM-5/WO3-Pt) displaying a synergistic effect for ethylene removal. The hydroxyl radicals caused by WO3-Pt migrate into the micropores of the ZSM-5 matrix. These facilitated both adsorbing and decomposing ethylene during fruit storage without requiring a circulation device. The ZSM-5/WO3-Pt powders were processed with organic binder-free granules using a drum rotary method, and ethylene removal capacity was studied by measuring the ethylene concentration, CO2, and increased humidity in Tedlar gas sampling bags. The practical applications were tested by evaluating the color change and degree of surface spoilage in tomatoes stored with and without ZSM-5/WO3-Pt; for more realistic conditions, this test was performed in a refrigerator. The results indicate the potential for successful commercialization of this system.
Keywords: Environmental wastes; Ethylene concentration; Fruits and vegetables; Maintaining freshness; Morphological characteristic; Photocatalytic oxidations; Realistic conditions; ZSM-5; Ethylene removal; Maintaining freshness; Photocatalysts; WO3; Zeolite; ZSM-5